Katz index of activities of daily living in assessing functional status of older people: Reliability and validity of Sinhala version - Nirmala Rathnayake; Ruvini Karunadasa; Thilina Abeygunasekara; Warsha De Zoysa; Dhammika Palangasinghe; Sarath Lekamwasam (Elsevier, 2023)
Purpose: This study evaluated the reliability and validity of the Sinhala version of Katz index of activities of daily living (ADL) in assessing the functional status of older people aged >65 years. Materials and methods: The Katz index was translated to Sinhala, cross-culturally adapted and administered in two stages. In stage 01, 200 patients aged ≥65 years, selected randomly from out-patient medical clinics, were asked to fill the Sinhala version of Katz index along with the Sinhala version of the 10-item Barthel index (BI). The Katz index was re-administered after two weeks among a subgroup of 45 patients selected randomly. In stage 02, Katz index was administered among randomly selected 200 community dwelling older people, aged ≥65 years. In addition, performance-based physical functions [gait speed (GS) and short physical performance battery (SPPB)] were also measured. Results: The analysis of stage 01 data showed internal consistency measured with Cronbach's alpha of 0.82 and test-retest reliability evaluated with intra-class correlation (ICC) (95% CI) of 0.94 (0.89-0.96) (p < 0.001). Exploratory Factor Analysis with the Principal Component Analysis revealed the presence of two factors with Eigen value exceeding 01, explaining 75.9% of cumulative variance. Further, the Sinhala version of Katz index total score showed a strong correlation with the BI total score (r = 0.91, p < 0.001) indicating strong concurrent validity. The stage 02 data revealed that older people with poor perception of general health status had lower mean (SD) Katz index score (3.58 ± 1.82) compared to those with good perception of health (5.56 ± 0.79) (p < 0.001). Similarly older people with prevalent diseases had comparatively lower scores of Katz index, compared to those without, indicating the known group validity (p < 0.05). Further, moderate correlations between the Katz index and performance based physical functions were observed showing the agreement (with GS - r; −0.26, p < 0.001, with SPPB - r; 0.31, p < 0.001). Conclusions: We conclude that the Sinhala version of Katz index has satisfactory psychometric properties and it is a reliable and valid tool to assess the functional status of Sinhala conversant older people in Sri Lanka.